2022
DOI: 10.1007/s00784-022-04560-4
|View full text |Cite|
|
Sign up to set email alerts
|

Force delivery modification of removable thermoplastic appliances using Hilliard precision thermopliers for tipping an upper central incisor

Abstract: Objectives To evaluate the force delivered by removable thermoplastic appliances (RTAs, aligners), altered with Hilliard precision thermopliers, on an upper central incisor to tip it in the palatal and vestibular directions. Materials and methods A total of 10 aligners made from Ideal Clear® (polyethylene terephthalate glycol copolyester, PET-G) with a thickness of 1 mm were used in force analysis. Different-sized spot-thermoformed protuberances (bumps) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Another in vitro study 13 evaluated the force delivered by aligners modified through different-sized divots (heights from 0.022 to 0.142 mm) for tipping an upper central incisor in the vestibular and palatal directions. This study showed that a horizontal force of 0.35 to 0.60 N for tipping was reached with the divot of 0.041 mm height.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another in vitro study 13 evaluated the force delivered by aligners modified through different-sized divots (heights from 0.022 to 0.142 mm) for tipping an upper central incisor in the vestibular and palatal directions. This study showed that a horizontal force of 0.35 to 0.60 N for tipping was reached with the divot of 0.041 mm height.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study 12 has verified the ability of aligners by measuring forces and moments with 1 mm thick divots to control rotational movement of the central incisor when compared to aligners without divots. Another in vitro study 13 evaluated the force delivered by aligners modified through different‐sized divots (heights from 0.022 to 0.142 mm) for tipping an upper central incisor in the vestibular and palatal directions. This study showed that a horizontal force of 0.35 to 0.60 N for tipping was reached with the divot of 0.041 mm height.…”
Section: Introductionmentioning
confidence: 99%